An investigation into the impact of group consultation on the classroom behaviour of children with social, emotional and behavioural difficulties - Watson, Charlotta (2018)
Consultation is an increasingly common model of delivery in psychology services (Leadbetter, 2006; Sheridan et al., 2017). It provides group members with a chance to discuss, reflect and learn about shared hopes and concerns for an identified child (Farouk, 2004). While teachers’ positive ratings of consultations are consistent across much of the research (O’Farrell and Kinsella, 2018), there is a limited evidence indicating that group consultations impact positively on the focus child or reduce disruptive behaviours (Wilkinson, 2005; Garbacz et al., 2008; Upshur, Wenz-Ross & Reed, 2009; and Sheridan et al., 2012; Sheridan et al., 2017). However, much of the research that exists focused on the impact of consultation for children as a group rather than discussing its impact on the individual child (O’Farrell & Kinsella, 2018). The aim of this current study is, therefore, to investigate whether a series of group consultations, including parents and school staff, could improve the behaviour of three primary school children with social, emotional and behavioural difficulties. A case study design, incorporating a multiple baseline single case experimental design (SCED) was implemented. Repeated observational measures were taken to assess if there was an “indirect” impact of the consultations on the individual children’s classroom behaviour. The data was triangulated with pre-and post-measures of teacher perceptions of behaviour, assessed using Strength and Difficulties Questionnaire (SDQ; Goodman, 1997) and Child Behaviour Rating Scale (CBRS; Bronson et al., 1990). Following the conclusion of the consultations, interviews were held with members of staff and two of the pupils to offer supplementary qualitative data. This was analysed using thematic analysis in an attempt to explore how the consultations may have influenced the outcomes observed in each case. Drawing on the repeated observation measure, the results of the SCED demonstrated improvements in aspects of classroom behaviour for all three participants. In addition, this was supported by a positive change in SDQ and CBRS scores for two of the participants. School staff interviewed, also perceived there to have been a reduction in challenging behaviour. Staff also reported that the consultation process was helpful as a collaborative and supportive process. The study concluded that key school staff attending a series of group consultations can have a positive impact on classroom behaviour.